2011
DOI: 10.1021/ie200240e
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature H2S Removal with Metal-Doped Nanostructure ZnO Sorbents: Study of the Origin of Enhanced Reactivity in Cu-Containing Materials

Abstract: Sulfidation of pure and metal-doped ZnO nanostructure sorbents (M 0.03 Zn 0.97 O, M = Fe, Co, Ni, Cu) was studied in order to clarify the effect of metal on the transformation kinetics at 200À350 °C. The solids were prepared by coprecipitation from metal nitrate solution followed by calcination at 400 °C. Reaction with H 2 S was studied by thermal gravimetric analysis (TGA) using a gas mixture containing 0.2 vol % H 2 S in equimolar H 2 ÀN 2 . It was found that at 350 °C the TGA sulfidation profiles of all stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…We investigated the reactivity of ZnO towards a model organosulfur compound, thioacetamide. This choice was motivated by the use of oxides as solid-state adsorbents in desulfurization [37][38][39][40] and similar pollutant removal technologies. The reactivity of the oxide can be exploited for removing organosulfur compounds from hydrocarbon fuel streams by reactively adsorbing the organosulfur compound in the form of zinc sulfide (ZnS).…”
Section: Mayank Behl and Prashant K Jain*mentioning
confidence: 99%
“…We investigated the reactivity of ZnO towards a model organosulfur compound, thioacetamide. This choice was motivated by the use of oxides as solid-state adsorbents in desulfurization [37][38][39][40] and similar pollutant removal technologies. The reactivity of the oxide can be exploited for removing organosulfur compounds from hydrocarbon fuel streams by reactively adsorbing the organosulfur compound in the form of zinc sulfide (ZnS).…”
Section: Mayank Behl and Prashant K Jain*mentioning
confidence: 99%
“…This observation was consistent with the result obtained by Skrzypski et al in which their research shown that the fresh Cu/ZnO based-sorbent has a broad Cu XPS spectra and a narrow Cu peak was measured for the sulfide sample. 9) In addition to narrow and sharp feature, the binding energy of Cu shifts to lower energy (931.5 eV), indicating the appearance of Cu + in a sulfide environment. The Cu 2 S would be the main sulfide metal.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the assumption described above, doping of other oxides into ZnO particles may work [43]. Copper and Zn form many types of composite oxides and composite carbonates [67][68][69].…”
Section: Sample Preparation and Characterizationmentioning
confidence: 99%
“…This low reactivity of ZnO limits an application of ZnO to more acidic gases, e.g. SO x [41,42] and H 2 S [43,44]. Increasing the surface area enhances the reactivity of the oxide particles because of high surface to bulk ratio and increased steps and kinks on the surface [45,46].…”
Section: Introductionmentioning
confidence: 99%